Basics of CD8 T-cell immune responses after influenza infection and vaccination with inactivated or live attenuated influenza vaccine - Daniil Korenkov; Irina Isakova-Sivak; Larisa Rudenko (Taylor & Francis Group, 2018)
Introduction: One of the essential mechanisms of virus infection control is cell-mediated cytotoxicity, which can act in an antibody-dependent or -independent fashion and is provided by different effector cells. The role of CD8 T-cells in infection control and in affecting the pathological outcome of different types of infection has been demonstrated in numerous animal studies. Despite this, their role in controlling human influenza infection is not fully understood. Especially, knowledge about their induction and turnover in human influenza infection is limited. Differences in the development of CD8 T-cells after influenza infection or immunizations should be explored in detail, in relation to the bioaccessibility of influenza antigens, site of application and distribution routes. Areas covered: This review focuses on the basics of CD8 T-cell immune response both in human influenza infection and after administration of inactivated or live attenuated influenza vaccine. Some aspects of the accessibility, distribution and presentation of influenza antigens to CD8 T-cells are described. Expert commentary: The CD8 T-cell response is an essential connection between innate and antibody-mediated responses, which are all-important for influenza control. We hypothesize that immunization with live influenza vaccine is the most straightforward artificial way to induce an efficient influenza-specific CD8 T-cell response.